PENGARUH JENIS PENDIDIKAN DAN PERTIMBANGAN ETIS TERHADAP PERILAKU AUDITOR DAIAIIT SITUASI KONFLIK AUDIT PADA KANTOR AKUNTAN PUBLIK DI SURAKARTA - Pramesti, Hernawati; Satyawati, Endang (Jurnal Riset Akuntansi dan Keuangan, 2007)
This research to lookfor empirical evidence hit influtence mount education and ethical consideration harc an effect on to auditor behavior in conflict situation make an audit at KAP in Surakarta either through individwlly and also simultaneously. This research benefit to get better undcrstanding hit auditor behavior in situation kaflik make an audit of pursuant to storsy; level of education and ethical consideration. Technique of Data collecting by responder given kuesioner which consisted of 5 question. To measure data quality used a validity test with value of Conected ltem - Totalize Correlation and test reliabilitas with coeficient of Cronbach'S Alpha. Analyse data use doubled analysis regresi and the hypothesis examination with test t, F test, and classicassumption Result of uamination of hltpothesis that variab,le mount education have an effect on positive to auditor behavior in conflict situation make an audit of seen ttest (4,788) > t tables (1,70) sigfinancy (.000), ethical consideration have an efect on positive to auditor behavior in conJlict situationm&e an audit of seen t test (3,001) > t tables (1,70) signifinancy( .0A0 ). Result Ftest that variable mount education and ethical consideration ha,e an effect on positive at a time to auditor behavior in con- Jtict sitwtion make an audit at KAP in Surakarta seen that from F test (109.755) > F Tables (3,32) signijinancy ( .000 ). Conclusion -from analysis of data Hal, Ha2 And Ha3 proven that is mount education and ethical consideration have an effect on positive to auditor behavior in ,.tnflict situation make an audit of at KAP itt Surakarta either through individually and also simultaneously.Keywords : education, ethical consideration and auditor behavior in conflict situation make an audit.